1997
DOI: 10.1159/000185457
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Alpha and Tumorigenesis of the Endocrine Gland

Abstract: A point mutation in the protein kinase Cα (PKCα) gene has been discovered in a subpopulation of human pituitary tumors characterized by their invasive phenotype. Here we show that: (1) thyroid tumors can express the PKCα mutation detected in a subpopulation of follicular adenomas and carcinomas, and (2) mutated PKCα has modified enzymatic properties as compared to wild-type PKCα. It has lost its capacity to phosphorylate the S17R substrate and exhibits a higher sensitivity to degradation as compared to wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
1
6
0
1
Order By: Relevance
“…1D). Thus, one of the major cell biological defects of the PKCa-D294G mutant is the loss of tight membrane binding even upon treatment of TPA, consistent with the proposition by others that this mutant may have reduced stability of membrane association (5,9).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…1D). Thus, one of the major cell biological defects of the PKCa-D294G mutant is the loss of tight membrane binding even upon treatment of TPA, consistent with the proposition by others that this mutant may have reduced stability of membrane association (5,9).…”
Section: Resultssupporting
confidence: 87%
“…It is noteworthy that the PKCa-D294G mutant is found only in tumor cells with invasive behavior and elevated PKCa mutant protein levels but not found in the adjacent normal tissues (4,5). From our findings, it seems that PKCa-D294G mutant can influence the progression of endocrine tumors by severing the transduction of extracellular signals that are pivotal in the suppression of tumor growth and in the enhancement of apoptosis of cancer cells.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Corroborating our data, three other LOF PKC mutations have been previously described. A LOF PKCα mutation (D294G in C2 domain) was identified in three types of cancer (Alvaro et al, 1993; Prévostel et al, 1997; Zhu et al, 2005) and a LOF PKCζ mutation (S514F in the kinase domain) was identified in colorectal cancer (Galvez et al, 2009). A partial LOF mutation in PKCι (R471C), present in three distinct cancers, disrupted substrate binding and induced abnormal epithelial polarity (Linch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are no indications as to how Alvaro et al were able to identify tissues with low PKC activity relative to its high expression levels based on histone III-S phosphorylation, which contained the PKCa D294G mutation [9], as the same laboratory found no difference in the histone III-S phosphorylation of the mutated and wild-type PKCa [6]. In subsequent studies on thyroid tissues, the same group did not use the PKCa activity downregulation to find species with a mutation, and could not show that the PKCa mutation is characteristic of a distinct phenotype that characterizes a distinct type of thyroid neoplasias [7,29]. Therefore, the mutation of PKCa may be a secondary phenomenon in tissue neoplasias.…”
Section: Discussionmentioning
confidence: 99%